2013
DOI: 10.1111/faf.12023
|View full text |Cite
|
Sign up to set email alerts
|

Using flow guilds of freshwater fish in an adaptive management framework to simplify environmental flow delivery for semi‐arid riverine systems

Abstract: Freshwater rivers have been substantially altered by development and flow regulation. Altered hydrological regimes have affected a range of biota, but impacts are often most obvious on freshwater fish. Flow largely influences the range of physical habitat available to fish at various life history stages. Biological rhythms are therefore often linked to flow and optimized so that opportunities for spawning, growth and dispersal are synchronized. Assuming that flow therefore becomes the main factor which structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 78 publications
1
72
0
2
Order By: Relevance
“…to this end, it has been suggested that environmental flow delivery in semi-arid riverine systems over long-term time-frames should consist of a combination of a few large, overbank flood pulses and several small, in-channel flow pulses, rather than a single (flood) pulse to be delivered e.g. on an annual basis, dependent upon water availability (vilizzi 2012; Baumgartner et al 2013). On the other hand, whilst these environmental flow delivery strategies are likely to benefit the native fish community by addressing the diverse species-specific range of spawning and recruitment habitat requirements, they are unlikely to limit wetland habitat use and exploitation by carp (Conallin et al 2012).…”
Section: Management Considerationsmentioning
confidence: 99%
“…to this end, it has been suggested that environmental flow delivery in semi-arid riverine systems over long-term time-frames should consist of a combination of a few large, overbank flood pulses and several small, in-channel flow pulses, rather than a single (flood) pulse to be delivered e.g. on an annual basis, dependent upon water availability (vilizzi 2012; Baumgartner et al 2013). On the other hand, whilst these environmental flow delivery strategies are likely to benefit the native fish community by addressing the diverse species-specific range of spawning and recruitment habitat requirements, they are unlikely to limit wetland habitat use and exploitation by carp (Conallin et al 2012).…”
Section: Management Considerationsmentioning
confidence: 99%
“…Clearly, from a management and conservation perspective orientated especially toward the implementation of water allocation programs, the presence of a 'mosaic' of species may limit, to some extent, the effectiveness of flow delivery scenarios, such as those proposed for Hypseleotris spp. (Baumgartner et al, 2014), and as recently testified by the lower accuracy achieved in predictions for this species complex from decision support tools for the management of inundation events (Vilizzi et al, 2013). Given the documented presence of several other species complexes in the freshwater fish fauna of river systems, a better matching of taxonomy with ecology becomes essential for the successful management and conservation of species complexes.…”
Section: Management Considerationsmentioning
confidence: 99%
“…Clearly, for the successful implementation of such intervention measures, an extensive knowledge of the ecology and biology of fish fauna is essential. However, in the case of Hypseleotris spp., despite its recent categorization as a foraging generalist with a spawning season lasting from September to April (Baumgartner et al, 2014), more extended spawning periods have been reported (Vilizzi, 2011(Vilizzi, , 2012, and predictive models for managed inundation events have resulted in lower accuracy compared to other species (Vilizzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stock enhancement has been undertaken in the Murray-Darling Basin region of Australia for over 100 years (Barwick et al 2014); an area where native fish species are estimated at less than 10% of pre-European levels . Some species have declined further, many unsighted for almost 40 years in areas where they were historically abundant (Baumgartner et al 2014). Originating as a simple trap and relocation program (Anderson 1915), the stock enhancement program is now coordinated by individual state agencies across the entire catchment in collaboration with government, anglers and private hatcheries.…”
Section: Introductionmentioning
confidence: 99%